Dual labour markets revisited - Bentolila, Samuel; Dolado, Juan José; Jimeno, Juan F. (Munich, 2018)
"This paper provides an overview of recent research on dual labour markets. Theoretical and empirical contributions on the labour-market effects of dual employment protection legislation are revisited, as well as factors behind its resilience and policies geared towards correcting its negative consequences. The topics covered include the stepping-stone or dead-end nature of temporary contracts, their effects on employment, unemployment, churn, training, productivity growth, wages, and labour market inflows and outflows. The paper reviews both theoretical advances and relevant policy discussions, in particular in several countries that had very poor employment performance during the recent global economic and financial crisis."